GAME BASED ENTREPRENEURSHIP LEARNING FOR VOCATIONAL HIGH SCHOOL STUDENTS IN FACING 4.0 INDUSTRY - Indra Febrianto; Heny Kusdiyanti; Chau Kien Tsong (Universitas Negeri Malang, 2021)
This study aims to analyze game-based entrepreneurship learning conducted on vocational high school students in facing Industry 4.0. This research used a literature review method with descriptive analysis through the provision of clear, factual, logical, and systematic discussion. This research used content analysis. The results of this study suggest that technology implementation is unquestionably required in the entrepreneurship learning process for the attainment of students' competences in the 4.0 Industry. Those competencies include social skills, one of the cross-functional skills, in the 4.0 Industry era that can be implemented through social entrepreneurship. In addition, game-based learning is effective to be applied to offer new different learning experiences. Those experiences are 1) learning by doing, 2) reflective learning, 3) situated learning, and 4) learning from crises. This learning is an alternative solution to prepare vocational high school students to encounter the 4.0 Industry.